(untitled) (CIPEEX, 2025)
ABSTRACT The 1988 Constitution defines the Public Prosecutor’s Office (MP) as essential to the jurisdictional function of the democratic state. In the electoral context, the Electoral Public Prosecutor’s Office (MPE) is composed of members of both the Federal and State Public Prosecutor’s Offices. The objective of this study is to analyze the role of the MPE in the Brazilian electoral process, identifying its performance, limitations, and current challenges. The method used was bibliographic and documentary research, based on relevant legislation and institutional manuals. The results indicate that the MP has legitimacy to act in all stages of the electoral process, from the registration of candidacies to the certification of elected candidates. However, it faces significant challenges, such as certain electoral crimes, combating electoral corruption, abuses of political and economic power, as well as current issues such as electoral disinformation. The MPE has structural and normative limitations, such as the lack of its own structure and the delegation of Federal Public Prosecutor’s Office functions to the MPE in the first instance. Recent initiatives, such as CNMP Resolution No. 297/2024, promote the integrated action of the MPE with other institutions, such as the Special Action Groups to Combat Organized Crime (GAECOs), with the goal of combating the influence of criminal organizations in the electoral process. It is concluded that the MPE is fundamental to ensuring the integrity of the electoral process in Brazil. However, to face contemporary challenges, it is imperative to strengthen its structure, promote continuous training, and foster integration with other institutions, thereby ensuring the effectiveness of its constitutional mission within the electoral system.